Independent assessment of bachelor’s quality - Andrey V. Belotserkovsky; Lyubov A. Kravtsova; Anton V. Dozhdikov (Высшее образование в России)
The article contains a summary and the conclusions of a research project associated with the assessment of the quality of undergraduate study and the possibility for using these results as the admission procedures to a master course. The results of the project can be used to implement public policies to improve the quality of higher education.